Political science of the future - Vodovnik, Žiga (Teorija in praksa, 2024)
The article presents an attempt to make sense of Adolf Bibič’s oeuvre as a whole. It reveals his broader intellectual (and also political) project along with his coherent and systematic analysis of what may also be understood as the ‘possibilities’ of political science. We claim that Bibič’s various analyses and interventions actually pivot on the question of the future or, even better, the role and position of political science in it. We name this aspect of Bibič’s oeuvre the ‘political science of the future’, which necessarily returns to the history of political ideas and political history to even be able to understand the current political relations and their contradictions. The ambition and capacity of the ‘political science of the future’ is not merely an explanation of what exists since, as Bibič states, political science is the key science for facing the challenges of the future and, accordingly, vital for our existence – political and physical.
Keywords: Bibič, Adolf; citizenship; democracy; demokracija; država; državljanstvo; future; Napovedovanje; Politične vede; prihodnost; state